Characterization of the extracellular matrix of Phaeodactylum tricornutum (Bacillariophyceae): structure, composition, and adhesive characteristics. Issue 5 (3rd September 2013) - Willis, Anusuya; Chiovitti, Anthony; Dugdale, Tony M; Wetherbee, Richard; Mock, T.
<x xml:space="preserve">Abstract</x> The extracellular matrix of the ovoid and fusiform morphotypes of Phaeodactylum tricornutum (Bohlin) was characterized in detail. The structural and nanophysical properties were analyzed by microscopy. Of the two morphotypes, only the ovoid form secretes adhesive mucilage; light microscopy and scanning electron microscopy images showed that the mucilage was secreted from the girdle band region of the cell as cell‐substratum tethers, accumulating on the surface forming a biofilm. After 7 d, the secreted mucilage became entangled, forming adhesive strands that crisscrossed the substratum surface. In the initial secreted mucilage atomic force microscopy identified a high proportion of adhesive molecules without regular retraction curves and some modular‐like adhesive molecules, in the 7 d old biofilm, the adhesive molecules were longer with fewer adhesive events but greater adhesive strength. Chemical characterization was carried out on extracted proteins and polysaccharides. Differences in protein composition, monosaccharide composition, and linkage analysis are discussed in relation to the composition of the frustule and secreted adhesive mucilage. Polysaccharide analysis showed a broad range of monosaccharides and linkages across all fractions with idiosyncratic enrichment of particular monosaccharides and linkages in each fraction. 3‐linked Mannan was highly enriched in the cell frustule fractions indicating a major structural role, while Rhamnose and Fucose derivatives were enriched in the secreted fractions of the ovoid morphotype suggesting involvement in cell adhesion. Comparison of SDS‐PAGE of extracellular proteins showed two major bands for the ovoid morphotype and four for the fusiform morphotype of which only one appeared to be common to both morphotypes.